Energy of its relation to academic collectability for Education college Students at Blue Nile University (Quality study) - Ali, Ibrahim Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to knowing energy and its relation to academic collectability for Education college students at Blue Nile University. The researcher adopted analytical descriptive method and inductive one in the study procedures. The sample curtained (22) informant’ (11) teaching Staff’ and (11) Students. The researcher sued documents analysis. and the interview as tools for information gathering. The Study consist of introduction’ (6) chapters’ and conclusion ’where the first chapter broached energy in the academic collectability for Education College Students at Blue Nile University. And in the Second chapter to energy weakness reasons’ and in the third one to energy relation with academic collectability’ and in the fourth one to energy role in academic collectability’ and in the fifth one to the student’s characteristics who has high energy and low one’ and in the sixth one to development mechanism of student’s energy to academic collectability. Finally, the corclwsim which included man results gist, recommendations, and suggestions. The study showed that there is relation between energy and academic collectability for Education college students at Blue Nile University. Also, energy has big role in academic collectability. according to the study’s result, the researcher represented recommendation to teachers of Education college at Blue Nile University about energy relation academic collectability for the students, and its reflections on graduates’ result. Moreover, recommendation to parents to communicate with Education college to intermonth their son’s academic collectability. The researcher represented to make studies in notability and its relation with academic collectability according to successful student’s view point, and students in energy between men and women at Education college at university.